PENGARUH KOMUNIKASI MANDOR TERHADAP KINERJA KARYAWAN PADA PT. DEWITA SAWIT NUSANTARA - Irfan Maulana; Nur Hidayat; Budi Winarni; Daryono; Rusmini (Politeknik Pertanian Negeri Samarinda, 2019)
Effect of Foreman Communication on Employee Performance at PT. Dewata Sawit Nusantara. This research is motivated by a number of cases of violence that occurred against the foreman, especially in the secretariat of oil palm plantations which caused the death of the foreman itself and automatically work in the palm oil sector will be hampered or decreased production even followed by poor quality of the oil palm plant itself. Of the several cases that occurred due to miscommunication between the foreman and the employee causing conflicts that triggered emotions on both sides. To support this research, the method of distributing questionnaires to respondents who have been chosen is chosen and not to forget the direct observation in the field and then supported by company data which is then processed in statistical tests to determine the effect of foreman communication on employee performance. It can be seen from the results of this study that good communication attitude from the foreman greatly influences the quality of employee performance and of course must also be supported by the good social adaptation abilities of the foreman.